Macroeconomic Interaction and Regional Development Inequality: An Empirical Study of South Sumatra from an Islamic Economic Perspective - Aldi, Soni; Malik, Anas; Rahman, Taufiqur (Indonesian Journal of Islamic Economics and Finance, 2025)
This study aims to analyze how the influence of local government spending, regional inflation and unemployment rates open to regional development inequality in sumbagsel in the perspective of Islamic Economics in 2015-2023”. The type of research used in this study uses a quantitative approach with panel data analysis methods. Data obtained through the Central Bureau of Statistics, Ministry of Finance and analyzed using the T test and F test to determine each independent variable to the dependent, namely inequality of regional development. Based on the analysis, partially government spending, inflation, and unemployment do not significantly affect the inequality of development in Sumbagsel. However, all three variables simultaneously have a very significant effect on inequality, suggesting that the complex interplay of these factors is a key driver of regional disparities. These findings affirm the importance of local governments to implement holistic and integrated policies in accordance with Sharia economic principles, which focus on equitable distribution of resources and the creation of equitable welfare.